Consumer engagement with football brands on social media : a comparison between Cruzeiro EC and FC Porto - Lodi, Rodrigo Caldas (2021)
Social networking sites (SNS) are an essential part of our current society with a countless number of SNS emerging all over the world. Many of these platforms have distinct functionalities, and for that reason, users can have different interactions in each of them. Due to their global popularity, SNS have drawn the attention of marketers as they are a space where brands can develop a closer relationship with their consumers. This research focuses on the interactions of consumers with football brands on SNS. By analysing consumer-brand engagement on Facebook, Twitter and Instagram we were able to identify five primary motivations that drive interaction with football brands on each of these SNS: Social-Interaction, Information-Seeking, Passion, Entertainment and Incentive. Our findings suggest that football fans have different motives for engaging with football brands on each of the three SNS studied. Furthermore, our study also analysed the dissimilarities between consumer-brand engagement on the SNS pages of FC Porto and Cruzeiro EC. The results indicate that the supporters of each club have different motivations for contributing and consuming content on their favourite football brands’ pages on Facebook, Twitter and Instagram.